Страховочное приспособление для аппарата электрошлаковой сварки, применяемого в машиностроении - Диордийчук, В. В. (НТУ "ХПИ", 2008)
У статті приведений аналіз різних конструкцій апаратів, що вживаються для електрошлакової зварки на машинобудівному підприємстві. Розглянуті конструкції цих апаратів. Зроблений аналіз недоліків конструкцій апаратів за ступенем надійності їхньої роботи при зварці. Детально описана конструкція страхувального пристосування, що збільшує надійність апарату типа АШ-115М.

In the article the analysis of different constructions of welding apparatus is conducted applied for the electroslag welding at machine-building enterprise. The constructions of these apparatus are considered. The analysis of construction lacks of apparatus on the degree of their reliability at welding is done. The construction of safety adaptation whichincreases reliability of apparatus of AS-115M typeis described in detail.
Keywords: узлы; опорные кольца; радиус кривизны; приводная шестерня